PENGARUH MOTIVASI KERJA TERHADAP KINERJA PRAMUGRAHA DI HARRIS HOTEL & CONVENTIONS KELAPA GADING - Imam Ardiansyah; Endah Fitriyani; Fahry Ahmad (Jurnal Inovasi Penelitian, 2021)
This research aims to find out if work motivation (x) affects the performance of employees (y) sales people at Harris Hotel & Conventions Kelapa Gading. This research includes quantitative research using validity tests, reliability, classic assumption tests, simple linear regression and determination coefficient tests. The sample in this study amounted to 30 respondents with saturated sample techniques, which is the technique of sampling when all members of the population are relatively small, fewer than 30 people or studies who want to generalize with very small mistakes. Another term of saturated sample is census, where all members of the population are sampled. The data collection techniques used are observation methods and questionnaires. The results of the study that Work Motivation had a significant effect supported by the dimensions of Physical Needs and Self-Actualization Needs that had a significant influence on the Performance of The Maid with a simple linear regression equation value of Y = 3,196 + 0.226 . The advice given to the company is to conduct a briefing to the sales people of Harris Hotel & Conventions Kelapa Gading in developing work motivation and maintaining and improving the performance of the work that has been given.